Computer Software and Hardware Complex for Personal Oral Speech Restoration after a Stroke - Vovk, M.I.; Halian, Ye.B.; Kutsiak, O.A. (Science and Innovation, 2024)
Introduction. The speech disorders are one of stroke consequences, among which motor aphasia occupies a significant place. Problem Statement. Synthesis of effective methods and means of oral speech restoration is an urgent scientific and practical task. Purpose. To develop a computer complex for oral speech restoration of mass application. Materials and Methods. Structural-functional modeling, myostimulation, mathematical apparatus of predicate logic, C# and ActionScript 2.0 programming languages. Results. The PROMOVA-2 computer software & hardware complex for personal speech restoration has been developed. It uses the innovative technology of speech restoration based on movements training of the affected hand and fingers after stroke. The complex consists of TRENAR® electronic devices for training motor functions of the affected hand by different methods and programs of myostimulation and ProMova 1.2 software module in the PC structure. ProMova 1.2 contains the unit for speech disorders diagnostics, which uses software for quantitative assessment of motor and sensory components of speech; the unit to help a doctor in the formation of personal plan for training of affected hand proceeding from the results of diagnostics; the patient’s medical records database, and the knowledge base with information on the operation of TRENAR® devices and hand training techniques. The supporting documents (guidance on the practical use of PROMOVA-2 and user manual of the ProMova 1.2 module) will facilitate the mass use of the complex. The results of the clinical trial have shown a greater efficiency of the innovative speech restoration method implemented using the complex as compared with the basic rehabilitation course. Conclusions. The PROMOVA-2 computer hardware & software complex for personal oral speech restoration performing several functions (diagnostics, speech restoration, and speech restoration knowledge transfer) may be recommended for mass use.